Open Dialogue: A case study on the influence of sharing or withholding reflections during a network meeting - van Dieren, Albert; Clavero, Corine (Frontiers in Psychology, 2022)
Sharing reflections by the professionals is in Open Dialogue an important contribution to promote a polyphonic dialogue between participants. In the inner dialogue, past and future influence the present moment. In this article we explored the influence of sharing or withholding reflections by professionals on the interplay between inner and outer dialogue. A case study was used with a multi-perspective methodology, which combined video recordings of a network meeting and interviews by using video stimulated recall with the clients separate and social workers together afterwards. We found that the sharing of reflections by professionals stimulates the inner dialogue and gives an opening to share those in the outer dialogue. In addition, we noticed that when reflections are withheld that the inner dialogue of the clients still continues, but their inner dialogue was not shared in the outer dialogue.